TRANSLATING METHODS FOLKLORE TITLED â€œNYI RORO KIDULâ€ FROM ENGLISH TO INDONESIAN - I Putu Hendrawan; I Gusti Nyoman Putra Kamayana (LPPM Universitas Dhyana Pura, 2023)
This research aims to analyze the translation methods found in the folk tale â€œNyi Roro Kidul.â€According to Newmark's (1988) classification, translation strategies can be categorized intoprocedures and methods, with the research specifically focusing on methods. Employing aqualitative descriptive approach, the study analyzes data derived from words, phrases, andsentences in the Nyi Roro Kidul folklore. Unlike participant interviews, the data collectioninvolves observation and recording from English (SL) to Indonesian (TL). The findings revealthe presence of eight translation methods in the Nyi Roro Kidul folklore: Word-for-Wordtranslation, Literal translation, Faithful translation, Adaptation, Semantic translation, Freetranslation, Idiomatic translation, and Communicative translation. The most frequentlyobserved methods in the data are Adaptation and Free Translation.